Structural and spectroscopic studies of hydroxyapatite nanorods Formed via microwave-assisted synthesis route - Mishra V.K.; Srivastava S.K.; Asthana B.P.; Kumar D. (My University, 2025)
In the present investigation Hydroxyapatite [Ca 10(PO 4) 6(OH) 2:(HAp)] nanorods were synthesized using microwave irradiation technique taking ethylene diamine tetra-acetic acid as a complexing reagent. Hydroxyapatite precursor obtained using microwave irradiation was subjected to differential thermal analysis. Later it was calcined in the temperature range 450°C-900°C. The crystal, grain, and bonding structures of resulting HAp were characterized structurally using X-ray diffraction and scanning electron microscopy (SEM) techniques and spectroscopically using Fourier transform infrared (FT-IR) and Raman techniques. The structural and spectroscopic characterizations of precursor revealed the formation of hydrated HAp. SEM images of the specimens calcined at 600°C and 900°C are presented. This study clearly reveals that nanorods are not formed below 700°C and nanorods are formed only after heat treatment of HAp precursor at 700°C and above. The diameter of nanorods was estimated to be ∼200 nm. No nanostructures were found to be formed if the precursor is calcined below 700°C. FT-IR and Raman spectra of HAp samples obtained after calcinations at 700°C and above further confirm the formation of HAp nanorods. © 2012 The American Ceramic Society.